Layanan Sosial Layanan Sosial dan Pemenuhan Hak Anak Studi di Lembaga Kesejahteraan Sosial (LKSA) Al-Hidayah - Asril, A. Fernandos; Pramono, Wahyu; Jendrius (Jurnal Administrasi Publik dan Pemerintahan, 2024)
here are still various problems in providing social services and fulfilling children's rights at LKSA AlHidayah. These problems include inadequate quality of service facilities and infrastructure, incompetent workers, and limited budget. The purpose of this study is to describe the types of social services and fulfillment of children's rights in LKSA Al-Hidayah. This research approach is qualitative with a descriptive type. Research informants were selected using purposive sampling techniques, in data collection using observation techniques, in-depth interviews, and document studies. The results of the study indicate that the types of social services in LKSA Al Hidayah include: 1) basic services (clothing, food, and shelter), 2) psychological services, 3) educational services, 4) health services, 5) recreation and entertainment services, 6) skills and talent development services, 7) spiritual services, and 8) transportation services. Six of the eight types of social services provided are quite good, while the quality of psychological and transportation services is not good enough. The fulfillment of children's rights in this LKSA includes: 1) the right to life, 2) the right to growth and development, 3) the right to protection, 4) the right to education, 5) the right to health, 6) the right to participation, 7) the right to identity, 8) the right to freedom of expression, 9) the right to receive equal treatment, and 10) the right to play and relax. Nine of the ten children's rights have been fulfilled well. However, the right to participation has not been fulfilled well.